ANALISIS PENGARUH SIKAP YANG DIMODERASI OLEH KEINOVATIFAN KONSUMEN TERHADAP INTENSI MEMBELI PRODUK BUSANA MUSLIM TANIAZ DI KABUPATEN JOMBANG - Cecia Rahmadani; Rofi aty (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to analyze the influence of attitudes moderated by the innovativeness of the intention to buy products Moslem Taniaz in Jombang. To determine how much influence the independent variable (attitude) that is moderated by innovativeness variable on the dependent variable ( intention to buy ) used regression analysis with t test analysis method and f. This study used a sample of 100 respondents who have the intention to buy the products Taniaz Muslim fashion. While the sample using accidental sampling technique. The results using  moderated  regression analysis  (MRA)  to test showed that the simultaneous interaction of attitudinal variables (X1), innovativeness  (X2), and attitudes moderated  by consumer keinovatifan (X1X2) has a significant influence on purchase intention (Y). While partial, attitudinal variables (X1), innovativeness  (X2) and attitudes moderated by innovativeness  (X1X2) has a significant influence on purchase intention (Y).Keywords: Attitude, Innovativeness, Intention to buy